2021
DOI: 10.1111/jce.14846
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guided axillary vein access: An alternative approach to venous access for cardiac device implantation

Abstract: Introduction Ultrasound guided axillary vein access (UGAVA) is an emerging approach for cardiac implantable electronic device (CIED) implantation not widely utilized. Methods and Results This is a retrospective, age and sex‐matched cohort study of CIED implantation from January 2017 to July 2019 comparing UGAVA before incision to venous access obtained after incision without ultrasound (conventional). The study population included 561 patients (187 with attempted UGAVA, 68 ± 13 years old, 43% women, body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 25 publications
6
28
1
Order By: Relevance
“…[9,10,[14][15][16][17][18][19]), our results paralleled the most recent literature on ultrasound-guided AV access for the same procedure type. Indeed, although the studies were somewhat different in ultrasound-guided venipuncture techniques and ultrasound system machines (i.e., on-cart, portable, or wireless), the success rate proved similar across the patient groups with USGAVA, including our procedures performed by a handheld device [9,10,[14][15][16][17][18][19]. Conversely, the complication rate was quite different between studies, probably affected either by the different follow-up duration or the broad definition of procedurerelated complications, as some of these were unlikely related to the venous cannulation technique.…”
Section: Comparison With Other Recent Usgava Experiencessupporting
confidence: 85%
See 2 more Smart Citations
“…[9,10,[14][15][16][17][18][19]), our results paralleled the most recent literature on ultrasound-guided AV access for the same procedure type. Indeed, although the studies were somewhat different in ultrasound-guided venipuncture techniques and ultrasound system machines (i.e., on-cart, portable, or wireless), the success rate proved similar across the patient groups with USGAVA, including our procedures performed by a handheld device [9,10,[14][15][16][17][18][19]. Conversely, the complication rate was quite different between studies, probably affected either by the different follow-up duration or the broad definition of procedurerelated complications, as some of these were unlikely related to the venous cannulation technique.…”
Section: Comparison With Other Recent Usgava Experiencessupporting
confidence: 85%
“…As shown in Table 3 (Ref. [9,10,[14][15][16][17][18][19]), our results paralleled the most recent literature on ultrasound-guided AV access for the same procedure type. Indeed, although the studies were somewhat different in ultrasound-guided venipuncture techniques and ultrasound system machines (i.e., on-cart, portable, or wireless), the success rate proved similar across the patient groups with USGAVA, including our procedures performed by a handheld device [9,10,[14][15][16][17][18][19].…”
Section: Comparison With Other Recent Usgava Experiencessupporting
confidence: 84%
See 1 more Smart Citation
“… 13 Chandler et al reported that, in a cohort study of 561 patients, US-guided axillary vein access before incision was safe and could help prevent an extra incision if a barrier is identified that necessitates a change in laterality. 14 …”
Section: Discussionmentioning
confidence: 99%
“…These approaches remain popular, perhaps due to operators' reluctance to adopt a new technique in the absence of a randomized trial to support a substantial benefit. Chandler et al [7] present their retrospective experience of US-guided access for transvenous device implantation from a single center. This study's results are significant, showing a 95% success rate with US guidance regardless of laterality.…”
mentioning
confidence: 99%